CRONY CAPITALISM AND POST-CRISIS ECONOMY IN INDONESIA AND THE PHILIPPINES - Maretta Kartika Sari (Jurnal Kajian Wilayah, 2016)
Crony capitalism is one main feature of the ersatz capitalism. Indonesian and Philippines, two East-Asian countries which are categorized by scholars in the same group practicing the form of ersatz capitalism system, respectively had undergone a historical period of robust authoritarian regime. This fact has indeed influenced the emergence of the strong cronyism in both countries. Through this article, we are briefly revisiting the experiences of Indonesia and Philippines during the Asian financial crisis 1997-98, focusing on their respective political reforms and the impact on the cronyism and eventually on the ability of both countries to survive the crisis. It is apparent that to a certain degree, the political reforms were indeed the key factor for both Indonesia and Philippines to outlast the hit of the Asian financial crisis in 1997-98. In other word, it was undeniably through a motion toward a more genuine capitalism system that these countries with that of ersatz capitalism could carry on against economic crises.AbstrakKapitalisme kroni merupakan salah satu fitur utama sistem kapitalisme semu. Sebagai negara Asia Tenggara yang dikenal memiliki sistem ekonomi yang disebut kapitalisme semu oleh para ahli, Indonesia dan Filipina sama-sama pernah mengalami periode sejarah kepemimpinan rezim otoriter yang turut membentuk kultur kapitalisme kroni yang kuat di kedua negara tersebut. Artikel ini memaparkan kembali secara singkat pengalaman Indonesia dan Filipina dalam menghadapi krisis moneter Asia tahun 1997-98, berfokus terutama pada reformasi politik dalam negeri masing-masing negara serta pengaruhnya terhadap kapitalisme kroni dan kemampuan negara mengatasi krisis. Tidak dapat dipungkiri bahwa reformasi politik di Indonesia dan di Filipina hingga taraf tertentu merupakan faktor kunci bagi kedua negara dalam mengatasi keterpurukan ekonomi akibat krisis keuangan Asia 1997-98 lalu. Dengan kata lain, Indonesia dan Filipina mampu mengatasi krisis ekonomi berkat langkah-langkah yang membawa sistem kapitalisme semu menjadi kapitalisme yang lebih murni.